The Study of Effect of the Active Layer Thickness on the Electrical properties of Organic Thin Film Transistor. - Nadhim Abduljaleel,Abdullah*1,Waleed Ali Hussain2; Hussain falih Hussain2. ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
In the present work, organic field effect transistor in TG-BC configuration was fabricated of Poly(3-hexylthiophene-2,5-diyl) (P3HT) as an active layer, and polyvinyl alcohol (PVA) as a gate dielectric layer. OFET was made at AL/PVA/P3HT/Au structure in constant conductance channel width (W=1mm) and length (L=60µm). The dielectric layer was deposited in constant revolution speed (1000rpm) by spin coating method, While the semiconducting polymer was deposited in multi revolution speeds (1000, 1500, 2000, 2500, 3000) rpm to obtain a different active layer thickness. All devices were worked in enhancement or accumulation mode. The best characteristic of the organic field effect transistor is when the thickness of an active layer corresponding to (2500rpm), which has the highest saturation mobility value (5.86x10-3 cm2/Vs) and (Ion/Ioff= 786), and lowest threshold voltage (-22V) and channel resistance (9.57x105 Ω).